2013
DOI: 10.1136/sextrans-2013-051186
|View full text |Cite
|
Sign up to set email alerts
|

STI testing without HIV disclosure by MSM with diagnosed HIV infection in England: cross-sectional results from an online panel survey

Abstract: Prevalence estimates of undiagnosed HIV among MSM may be inflated because some men with diagnosed HIV seek STI testing away from their usual care provider without disclosing their HIV infection or accepting an HIV test. Our data suggest that the reasons for doing so are convenience and discomfort about disclosing risky sexual behaviour to HIV care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This estimate is lower than that obtained (19%) from routine HIV testing among persons attending clinics for sexually transmitted infections (STI), in 2013 [ 18 ]. This estimate could be over-biased because of possible nondisclosure of HIV status due to convenience and discomfort in disclosing risky sexual behavior to healthcare professionals [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This estimate is lower than that obtained (19%) from routine HIV testing among persons attending clinics for sexually transmitted infections (STI), in 2013 [ 18 ]. This estimate could be over-biased because of possible nondisclosure of HIV status due to convenience and discomfort in disclosing risky sexual behavior to healthcare professionals [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of using online panels in studies include quick access to a large participant pool and targeted recruitment directed by available demographic data (Erens et al, 2014; Heeren et al, 2008). Directed recruitment can include panelists who live in certain geographical locations (Miller et al, 2017) and rare and dispersed populations like sexual minorities (Datta, Hickson, Reid, & Weatherburn, 2013; Sell et al, 2015). Some studies have demonstrated that using panel vendors to recruit a sample reflective of the national population that meet certain criteria, for example, adults between the ages of 18 and 40, can occur rapidly (Craig et al, 2013; Erens et al, 2014; Heeren et al, 2008).…”
mentioning
confidence: 99%
“…Datta et al 8 have taken this further, estimating the extent of STI testing away from usual HIV provider in a panel of MSM—this is relatively uncommon but not rare, though the extent probably varies by geography. The emergence of testing kits available over the internet will complicate STI prevention in this group still further.…”
mentioning
confidence: 99%